UV-Induced Photochemistry of 1,3-Benzoxazole, 2-Isocyanophenol, and 2-Cyanophenol Isolated in Low-Temperature Ar Matrixes - Reva, Igor (2021)
The monomers of 1,3-benzoxazole isolated in a cryogenic argon matrix were characterized by infrared spectroscopy. The photochemistry of matrix-isolated 1,3-benzoxazole, induced by excitation with a frequency-tunable narrowband UV light, was investigated. Irradiation at 233 nm resulted in a nearly quantitative conversion of 1,3-benzoxazole into 2-isocyanophenol. The individual photochemical behavior of the in situ produced 2-isocyanophenol was studied upon excitations at 290 nm, where 1,3-benzoxazole does not react. The photochemistry of isomeric matrix-isolated 2-cyanophenol was also studied. The photoreactions of 2-substituted (cyano- or isocyano-) phenols were found to have many similarities: (i) OH bond cleavage, yielding a 2-substituted (cyano- or isocyano-) phenoxyl radical and an H-atom, (ii) recombination of the detached H-atom, resulting in an oxo tautomer, and (iii) decomposition leading to fulvenone, together with HCN and HNC. In another photoprocess, 2-cyanophenol undergoes a [1,5] H-shift from the hydroxyl group to the cyano group yielding isomeric ketenimine. The analogous [1,5] H-shift from the hydroxyl group to the isocyano group must have also occurred in 2-isocyanophenol; however, the resulting nitrile ylide isomer is kinetically unstable and collapses to benzoxazole. All photoproducts were characterized by comparing their observed infrared spectra with those computed at the B3LYP/6-311++G(d,p) level. The mechanistic analysis of the photochemistry occurring in the family of the title compounds is presented.